G629(P) Involving children and young people in undergraduate paediatric education. (May 2019) - Morrissey, B; Wootton, L; Shea, T; Fernandes, K
Abstract : Aims: Children and young people (CYP) want to be involved in educating future health professionals, and for their voices to be heard. The General Medical Council encourages active involvement of patients in medical education, as it benefits both learners and patients. In paediatrics, this can be challenging to achieve partly as most CYP are at school when undergraduate teaching takes place. Methods: We filmed CYP speaking about their lives, living with a chronic medical condition, and their advice to future health professionals. With consent from CYP and their families, these were edited into short films, and incorporated into the paediatric teaching weeks. Students completed an anonymous questionnaire, evaluating whether these had any impact on their learning. Results: All medical students reported the films had an impact on them 'understanding what's important to children and young people' and 'providing context to the learning material.' 'It helped me think about the perspective of the patient.' 'I understand a bit more of what life is like for them.' 'How they're more than their condition.' ' They really helped to put things in context and engage me.' 'I remember better from patient stories.' 'They reinforced the learning points.' Eighty nine percent of students thought the films had an impact on their confidence communicating with CYP; in 55% this impact was 'considerable' or 'great.' ' Hearing young people detail exactly how to communicate with them is very useful.' 'Better understanding of what makes a consultation good for them. ' 'Makes dealing with children less intimidating.' Eighty nine percent of students thought the films had an impact on their motivation to learn paediatrics; in 64% this impact was 'considerable' or 'great.' Students would also like interviews with parents, and live sessions with CYP to ask questions. Conclusion: Short films of CYP talking about their lives and experiences of healthcare, and advice to future doctors, is an innovative way of involving CYP in undergraduate paediatric education, and positively affects students learning. Students gained skills in understanding the patient perspective, engaging and communicating with CYP, and they provided a context to the learning material, and motivated students to speak to CYP and learn paediatrics.